The Effect Of Foreign Language Ability (Arabic-English) On Students Learning Achievement (Qur’an And Hadith - Nadirah Usman; Syamsu T; Ibrahim Manda; Muhammad Fajar Akbar; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study at Darul Aman Gombara Makassar's border school, Buq'atun Mubarakah High School, aims to evaluate the effect of students' Arabic and English language competency on learning achievement, notably in the areas of the Qur'an and Hadith. The description provided by Imam Ghozali of the procedure for computing analysis data utilizing a multivariate analysis application with the IBM SPSS 25 program, edition 9 (2019). The results showed a link between knowledge of Arabic and English and academic success (as judged by the Qur'an and Hadith), with a significant value of 0.005. H0 is rejected and H1 is accepted, indicating that the hypothesis is true if the value is less than 0.05. The Arabic and English Language Ability and Learning Achievement (Qur'an and Hadith) variables are strongly associated with one another or match the necessary criteria, according to the correlation value of 0.512. A unidirectional link between the two variables is indicated by the correlation coefficient, which is 0.512 and positive. As a result, it is possible to say that a higher